The Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Sepatu Olahraga Futsal Specs (Studi Kasus pada Pengguna Sepatu Olahraga futsal Specs di Bandar Lampung) - Godho supriadi bimantoro (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2020)
This study aims to determine the effect of product quality on purchasing decisions for futsal sport shoes Specs in Bandar Lampung. This type of research is explanatory research. The number of samples used was 100 respondents. Sampling using probability sampling techniques with simple random sampling method. Data analysis techniques using the classical assumption test and multiple linear regression with the help of SPSS version 21. The results of this study partially have a significant effect between product quality (X2) on purchasing decisions (Y), the results of research simultaneously have a positive influence and significant between product quality (X2) on purchasing decisions (Y) with an R square value of 27.4%.